SOME LESS KNOWN ANTI-DIABETIC MEDICINAL PLANTS-AN EXPLORATION OF TRADITIONAL LORE AND EXPERIMENTS (AYUSHDHARA, 2017)
The fast growing Diabetes health problem is at risk to about 422 million estimated people in world scenario. As the people suffering from diabetes since ages and no definite medicine could be able to control the disease safely except insulin as a hope for sustaining life. Several herbal drugs are in practice for limited preventive and curative aspect. Ayurveda emphasize on the preventive aspects and provides managerial approach through lifestyle intervention since inception. Herbal products have always played vital role in drug research in every sphere. Several medicinal plants are being used in different way either by traditional healers or by practitioners in India and Abroad on the basis of known anti-diabetic activities but, so many other plants are there which are either used by traditional physicians which are not tested in the clinical laboratory and sometimes several medicinal plants have been tested as Anti-diabetic in R&D study but not known/less known to practitioners. In this paper attempts have been made to identify those medicinal plants with R&D experimental study but are less known to practitioners. Moreover such medicinal plants were also verified in classical references for anti-diabetic effect if any. The present paper deals with the comparison of classical references with modern R&D as far as possible. Review was focused on such limited number of medicinal plants which are commonly not known is having hypoglycemic effect. Observation was also noted through several experimental studies done by the scientists earlier which signifies the merit of study. Such herbal study models are attributed here to provide newer initiatives in future and it can also focus for better solution in the field of diabetes control.